Pengaruh Penggunaan Bioreaktor Dua Tahap terhadap Pengolahan Anaerobik Lindi Sampah Kota - Laily Isna Ramadhani; Alifa Dewi Kirana; Ghinaa Annisa Khairani; Herawati Budastuti; Dhyna Analyes Trirahayu; Keryanti (Jurnal Serambi Engineering, 2024)
The generation of waste in landfills can result in the production of wastewater, commonly referred to as leachate. This leachate has the potential to pollute the surrounding environment, as it can enter the groundwater or be transported by surface flows. Consequently, leachate treatment is conducted through a two-stage anaerobic process. The method was selected due to its capacity to decompose waste with high organic content and to produce optimal biogas. The objective of this study is to ascertain the impact of employing a two-stage anaerobic bioreactor on the proliferation of anaerobic microorganisms in the context of leachate treatment. The application of an acidic pH in the acidogenic bioreactor influences the growth of acidogenic bacteria, resulting in a shorter lag phase in comparison to the single bioreactor. This also impacted the reactor's performance in reducing the concentration of chemical oxygen demand (COD). The two-stage bioreactor demonstrated a superior COD reduction efficiency of 78%, in comparison to the single-stage bioreactor, which exhibited an efficiency of 69%.